Effects of Corn Silk Extract on Marshmallow Properties: Chemical and Physical Analysis - Paramitha Risnawati; Haslina; Dewi Larasati (Edusight International Journal of Multidisciplinary Studies, 2026)
Marshmallows are soft candies produced using gelling agents such as gelatin, pectin, or starch, and typically contain 12-20% water. Previous research has explored the incorporation of natural antioxidants into marshmallows, identifying corn silk as a particularly promising ingredient due to its high antioxidant content. This study investigates the impact of corn silk extract (Zea mays L.) on the physical and chemical properties of marshmallows. Employing a Completely Randomized Design (CRD) withfive treatments and four replications. the study varied the concentration of corn silk extract (10%, 20%, 30%, 40%, and 50%). The variables measured included water, ash, vitamin C, tannin, antioxidant activity, texture, and color. The results showed that corn silk extract variation had a significant effect (p< 0.05) on the chemical and physical properties of marshmallows including water, ash, sucrose, vitamin C, tannin, and antioxidant activity, texture and color. The best treatment was P5 (50% corn silk extract) with a vitamin C content of 62.87%. tannin 1.96%. antioxidant activity 55.8%, texture 136.16%, L color 65.48. a* color 6.42. and b* color 19.42. This study demonstrates the potential of adding corn silk extract to marshmallows to enhance their nutritional value and functional properties. The findings of this research can serve as a valuable reference for the development of healthier and more nutritious marshmallow products.